2018
DOI: 10.1002/qua.25649
|View full text |Cite
|
Sign up to set email alerts
|

Accurate spectroscopic constants of the lowest three electronic states in halonitrenes with multireference configuration interaction

Abstract: Internally contracted multireference configuration interaction (icMRCI) calculations of the ground state (X 3 R 2 ), the first excited state (a 1 D) as well as the second excited state (b 1 R 1 ) have been performed for a series of halogenated nitrenes NXs (X 5 Cl, Br, and I). Accurate spectroscopic constants of these lowest three electronic states of each NX were obtained in this work using MRCI methods with aug-cc-pVXZ (X 5 T, Q, 5) basis sets and complete basis set (CBS) limit. In addition, various correcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
(95 reference statements)
2
0
0
Order By: Relevance
“…It is indicated that as the basis set increases from aug-cc-pVQZ to CBS, the accuracy of the calculated spectroscopic constants is systematically improved. 40 Our results for the X 2 A″ and A 2 A′ states calculated at the icMRCI + Q/CBS level are in relatively good agreement with previous experimental and theoretical results.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It is indicated that as the basis set increases from aug-cc-pVQZ to CBS, the accuracy of the calculated spectroscopic constants is systematically improved. 40 Our results for the X 2 A″ and A 2 A′ states calculated at the icMRCI + Q/CBS level are in relatively good agreement with previous experimental and theoretical results.…”
Section: Resultssupporting
confidence: 90%
“…By comparing the results of aug-cc-pV5Z and those of CBS (Q5 extrapolation), we found that the values of bond lengths and ∠H–S–S of HS 2 converge in the magnitude order of 10 –2 Å and 0.01°, respectively. It is indicated that as the basis set increases from aug-cc-pVQZ to CBS, the accuracy of the calculated spectroscopic constants is systematically improved . Our results for the X 2 A″ and A 2 A′ states calculated at the icMRCI + Q/CBS level are in relatively good agreement with previous experimental and theoretical results.…”
Section: Resultssupporting
confidence: 87%